Positioning intellectual capital in ensuring personal and national security - Yu. A. Lozina; A. N. Litvinenko (Вестник университета, 2025)
Intellectual capital as a driving force of innovation economy proves the importance of the human resources quality in added value creation. The relevance of the research topic lies in the attempt to position intellectual capital in the situation of mismatch between the interests of a state and an individual in ensuring their security. The purpose of the study is to show the change in the intellectual capital position in ensuring personal and national security by methods of analysis and synthesis of concepts, processes, and phenomena. Ensuring a state’s national security includes scientific, technical, and technological components and search for talents for human potential development in order to realize state interests through ensuring the interests and needs of an individual. By pulling intellectual capital to its side, a state ensures effective development of national economy by increasing human potential and innovative leadership in international competition and forming new rules in the world from the soft power position. The presented results demonstrate that personal security, which was initially built on ensuring physical protection of an individual and the right to property, has gradually transformed into ensuring an individual’s rights in their abilities development. Ensuring an individual’s interests can be qualitatively improved with their intellectual potential development. In the struggle for creative abilities realization, not the state, but an individual begins to choose the conditions of personal security. In this regard, there is an increase in a state’s interest in the sphere of forming and incrementing human creative abilities for a state’s innovation capital growth.